2020
DOI: 10.3390/genes11080887
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis Using a Multi-Parent Wheat Population Identifies Novel Sources of Septoria Tritici Blotch Resistance

Abstract: Zymoseptoria tritici is the causative fungal pathogen of septoria tritici blotch (STB) disease of wheat (Triticum aestivum L.) that continuously threatens wheat crops in Ireland and throughout Europe. Under favorable conditions, STB can cause up to 50% yield losses if left untreated. STB is commonly controlled with fungicides; however, a combination of Z. tritici populations developing fungicide resistance and increased restrictions on fungicide use in the EU has led to farmers relying on fewer active substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 93 publications
3
28
1
Order By: Relevance
“…However, Miedaner et al (2013) detected a QTL on chromosome 6AS (14.2 cM) for STB APR in 1055 elite wheat hybrids and their 87 parental lines although quite far from the QTN detected in this study. Moreover, the current study detected other stable as well as environment-specific QTLs on chromosome arm regions including 1DS, 2BS, 3BL, 3BS, and 6BL in which most of them were reported previously by others including Riaz et al (2020) , but the 1DS and 3BL QTLs could be potentially newly discovered in this study for STB APR in wheat.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, Miedaner et al (2013) detected a QTL on chromosome 6AS (14.2 cM) for STB APR in 1055 elite wheat hybrids and their 87 parental lines although quite far from the QTN detected in this study. Moreover, the current study detected other stable as well as environment-specific QTLs on chromosome arm regions including 1DS, 2BS, 3BL, 3BS, and 6BL in which most of them were reported previously by others including Riaz et al (2020) , but the 1DS and 3BL QTLs could be potentially newly discovered in this study for STB APR in wheat.…”
Section: Discussionsupporting
confidence: 73%
“…The other stable marker detected in this study was BS00021714_51 (78 cM), according to Wang et al (2014b) on the long arm of chromosome 1A, which is nearby to the SNP marker wsnp_Ex_rep_c109742_92411838 (81 cM) discovered previously by Muqaddasi et al (2019) . Riaz et al (2020) also found a QTL on this chromosome region (70–78 cM) for STB resistance in winter wheat adult plants in the field. Chromosome 5A was the other region comprising a lot of SNP markers with stable and environment-specific highly significant QTNs for STB resistance including Kukri_c63163_141 that explained 8.0% from the total phenotypic variance.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Multi-parent Advanced Generation Intercrosses populations were conceived to improve precision and efficiency of QTL mapping in plants and animals as they allow overcoming limitations of biparental populations and association mapping panels ( Huang et al, 2015 ). In cereal crops, these experimental populations have been extensively used for research purpose and contributed to dissecting the genetic bases of several traits among which biotic stress resistance ( Stadlmeier et al, 2018 ; Jiménez-Galindo et al, 2019 ; Riaz et al, 2020 ), GY, grain quality ( Zaw et al, 2019 ) and DH ( Afsharyan et al, 2020 ). Recently, these genomic resources have been established in barley to investigate the effects of epistasis and environmental interactions on flowering time ( Mathew et al, 2018 ; Afsharyan et al, 2020 ), further broadening the original scope for which they were devised.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of these novel QTLs provided useful information that could be used to track favorable alleles for developing wheat cultivars resistant to STB. This knowledge can be used for generation of new allelic combination through cross between novel sources for resistance to STB (Riaz et al 2020). Lastly, some QTLs identi ed in this study were co-located with known STB genes or previously mapped Meta-QTLs for resistance to STB at the seedling and adult stages in the eld (Goodwin et al 2015;Goudemand et al 2013).…”
Section: Qtl Validation and Alignment To Previously Reported Stb Genes And Qtlsmentioning
confidence: 70%